Architecture, Innovation and Tradition. (8th January 2013) - Picon, Antoine
Abstract: Antoine Picon, Professor of the History of Architecture and Technology at Harvard Graduate School of Design (GSD), and the author of a significant new book, Ornament: The Politics of Architecture and Subjectivity (John Wiley & Sons), publishing in April 2013, provides the counterargument to this issue. He argues that for innovation to go beyond the superficial level of being a mere design trend or fashion, it needs to avoid 'presentism' and develop a reflexive stance to history and tradition.